Intervensi Pemerintah pada Kasus Balita Stunting di Desa Gunung Putri Kabupaten Pandeglang - Alda Amelia; Wahyu Kartiko Utami (Epistemik Press, 2024)
This research was motivated by the low food utilization index (52.59) compared to the high food availability index (91.55). The high prevalence of stunting (29.4%) in Pandeglang Regency also plays a role in the low utilization of food. This research uses the concept of food security from Pieters (2013) and the theory of *Decision Making: Non-Rational Theories* (2015) to understand how parents of stunted toddlers make decisions regarding daily eating patterns. Qualitative methods with a narrative approach were used in this research. The research results show that the decisions of parents of stunted toddlers are influenced by emotional and experiential factors, although economic factors remain the most dominant. To address the problem of food utilization, the Pandeglang Regency Government carried out specific and sensitive interventions through public education. However, efforts to combat stunting are hampered by budget constraints, which limit the number of field personnel and the reach of interventions. This research recommends an evaluation regarding the effectiveness of nutrition education programs as well as further research on socio-cultural factors that influence knowledge and application of nutrition in families with stunting toddlers.